Trabalhadores ambulantes e camelôs no centro de Aracaju : trabalho, precarirazação e (des) proteção previdenciária - Aragão, Maciela Rocha Souza (2013)
The present study aims to evaluate the work of hawkers / peddlers of Aracaju, as an activity that provides informal (or not) access to social welfare policy. Therefore, it was necessary to draw the socioeconomic profile of street vendors / hawkers who work at night and on Saturdays at Aracaju´s downtown, featuring the work of hawkers / peddlers while a segment of informal work and precarious condition; identify whether these workers contribute to social security and know the actions of the government, which contribute to the access of hawkers / peddlers to the ``formalization´´ and social security. Reference to the historical materialist dialectical method as a thread of theorizing and analysis presented here. The universe consisted of 64 workers affiliated to the Association of Autonomous Workers, Vendors and Craftsmen of the State of Sergipe and who are authorized by the Municipal Urban Services Company (EMSURB)/ Municipality of Aracaju to trade their goods in the city´s commercial center. Data collection was conducted through structured interviews, via the application of forms, 30 street vendors / hawkers, whose choice was defined by the following criteria: accessibility and / or convenience of the interviewee and authorization by signing the ``Consent free and Clear´´. Semi-structured interviews were also conducted with technical representatives of the following agencies: EMSURB, FUNDAT, SEBRAE and INSS. Its main results point to the fact that the precarious and informal employment in Brazil has historical relationship with the peculiarities of the labor market´s formation, which also led to the establishment of a system of wage labor, pension interdependent and regulated by the labor legislation. This historical relationship between formal employment and social security reflects the street vendors / hawkers from Aracaju´s downtown, who lack of social security protection, focusing, the nature of the occupation as inherent in the capitalist mode of production and the strategies created by government, which were not accessible or able to attract this segment of informal employment, given the nature contributory this policy.